Broadband availability in metropolitan and non-metropolitan Pennsylvania - Lawrence E. Wood (Netcom)
Over the past few years having a broadband connection has become essential for many Internet activities. As broadband increases in importance, it becomes imperative to assess how its use and availability may vary, especially in relation to issues such as geographic location. For rural areas in particular, the availability of broadband service is especially important. This research assesses broadband service availability in rural areas of Pennsylvania, USA. In particular, it examines the extent to which Digital Subscriber Line (DSL) and broadband cable modem services are being deployed throughout rural Pennsylvania. It compares this deployment with the availability of such services in the state’s urban and metropolitan areas. The results of this research suggest that there is a “digital divide” in terms of broadband availability between rural and urban areas of Pennsylvania. However, this “divide” is perhaps not as wide as might be expected. Thus, as broadband is becoming increasingly available in rural areas of the U.S. and throughout much of the rest of the world, this research concludes that while research must remain vigilant in terms of assessing advanced telecommunications availability in rural areas, future research should also be sure to focus on how such technologies can be used to promote economic and social concerns, including in relation to building online networks and diminishing social and professional isolation in rural areas.